Alu element insertion in the MLH1 exon 6 coding sequence as a mutation predisposing to Lynch syndrome. Issue 6 (21st May 2019) - Solassol, Jérôme; Larrieux, Marion; Leclerc, Julie; Ducros, Vincent; Corsini, Carole; Chiésa, Jean; Pujol, Pascal; Rey, Jean‐Marc
Abstract: Lynch syndrome (LS) is the most frequent cause of hereditary colorectal cancer. A subset of patients with a history of LS shows no causal germline pathogenic alteration and are identified as having Lynch‐like syndrome (LLS). Alu retrotransposons are the most abundant mobile DNA sequences in the human genome and have been associated with numerous human cancers by either disrupting coding regions or altering epigenetic modifications or splicing signals. We report a family first classified as having LLS by Sanger sequencing analysis. Next‐generation sequencing (NGS) analysis identified an AluY5a insertion in MLH1 exon 6 that led to exon skipping. This splicing alteration inducing a pathogenic frameshift was found in patients who developed colorectal adenocarcinomas. Retroelement insertion might thus be an important but underestimated mechanism of cancer genetics that could be systematically tested in patients with a phenotype suggesting LS to accurately assess family risk and surveillance approaches. Abstract :